“It's Like a Kick in the Teeth”: The Emergence of Novel Predictors of Burnout in Frontline Workers During Covid-19 - Sumner, Rachel C.; Kinsella, Elaine L. (Frontiers in Psychology, 2021)
The context of Covid-19 has offered an unusual cultural landscape for examining how workers view their own position relative to others, and how individuals respond to prolonged exposure to workplace stress across different sectors and cultures. Through our recent work tracking the wellbeing of frontline workers in the UK and Ireland (the CV19 Heroes project), we have uncovered additional psychological factors that have not been accounted for in previous models of occupational stress or burnout. In recent months, frontline workers have worked to protect the community from the threat of SARS-CoV-2 and, simultaneously, have evaluated their perceptions of collective efforts of others as either congruent or incongruent with collective goals (e.g., lowered mortality and morbidity): we call this novel aspect solidarity appraisal. These frontline workers have been hailed as heroes, which we argue has led to the creation of an implicit psychological contract (the hero contract) between frontline workers and the public. Here, the heroes are willing to ‘go above and beyond’ for the greater good, with the expectation that we (the public) do our part by adhering to public health guidelines. Where frontline workers perceive incongruence between the words and actions of others in working towards collective goals this drives negative affect and subsequent burnout. In this perspective article, we evaluate the cultural context of the pandemic in the UK and Ireland and suggest important socio-cultural factors that contribute to perceptions of solidarity, and how this may relate to burnout and worker welfare during and beyond the pandemic context.